Transcriptome Analysis of the Hierarchical Response of Histone Deacetylase Proteins That Respond in an Antagonistic Manner to Salinity Stress - Ueda, Minoru; Matsui, Akihiro; Watanabe, Shunsuke; Kobayashi, Makoto; Saito, Kazuki; Tanaka, Maho; Ishida, Junko; Kusano, Miyako; Seo, Mitsunori; Seki, Motoaki (Frontiers in Plant Science, 2019)
Acetylation in histone and non-histone proteins is balanced by histone acetyltransferase and histone deacetylase (HDAC) enzymatic activity, an essential aspect of fine-tuning plant response to environmental stresses. HDACs in Arabidopsis are composed of three families (RPD3-like, SIRT, and HD-tuins). A previous study indicated that class I (HDA19) and class II (HDA5/14/15/18) RPD3-like family HDACs control positive and negative responses to salinity stress, respectively. Furthermore, quintuple hda5/14/15/18/19 mutants (quint) exhibit salinity stress tolerance, suggesting that hda19 suppresses the sensitivity to salinity stress present in quadruple hda5/14/15/18 mutants (quad). In the present study, transcriptome analysis of the quint mutant was conducted to elucidate the hierarchical control of salinity stress response operated by RPD3-like family HDACs (HDA5/14/15/18/19). The analysis identified 4,832 salt responsive genes in wild type (Col-0), hda19-3, quad, and quint plants, and revealed that 56.7% of the salt responsive genes exhibited a similar expression pattern in both the hda19-3 and quint plants. These results indicate that deficiency in HDA19 has a bigger impact on salinity stress response than class II HDACs. Furthermore, the expression pattern of genes encoding enzymes that metabolize phytohormones raises the possibility that a drastic change in the homeostasis of phytohormones, such as abscisic acid, brassinosteroid, and gibberellin, may contribute to increasing stress tolerance in hda19-3 and quint plants. Among these phytohormones, abscisic acid accumulation actually increased in hda19-3 and quint plants, and decreased in quad, compared with wild-type plants. Importantly, 7.8% of the salt responsive genes in quint plants exhibited a similar expression pattern in quad plants, suggesting that some gene sets are regulated in an HDA5/14/15/18 dependent manner. The transcriptome analysis conducted in the present study revealed the hierarchical and independent regulation of salt stress response that is mediated through HDA19 and class II HDACs.